2013
DOI: 10.3329/ijarit.v1i1-2.13935
|View full text |Cite
|
Sign up to set email alerts
|

Development of Efficient Callus Initiation of Malta (Citrus sinensis) Through Tissue Culture

Abstract: The effects of different hormonal concentration on shoot formation and callus induction were studied on BARI Malta-1 (Citrus sinensis). Seeds containing seed coat and without seed coat was treated by Murashige and Skoog (MS) media supplemented with 6-benzyl adenine (BA) and Kinetin (KIN). Removal of seed coat showed an early response for shoot formation. The highest (70%) shoot formation was obtained from seeds without seed coat treated with MS basal media + BA 1.0 mg/l while KIN showed no response for shoot f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The explants were further sterilized with 0.1% HgCl 2 and Tween 20. Finally, the explants were dried on sterilized filter paper after washing several times with sterile distilled water [13]. The sterilized explants were inoculated in test tubes con-…”
Section: Methodsmentioning
confidence: 99%
“…The explants were further sterilized with 0.1% HgCl 2 and Tween 20. Finally, the explants were dried on sterilized filter paper after washing several times with sterile distilled water [13]. The sterilized explants were inoculated in test tubes con-…”
Section: Methodsmentioning
confidence: 99%
“…Removal of seed coat showed an early response for shoot formation. In case of sweet orange, highest (70%) shoot formation was obtained from seeds without seed coat (Azim et al, 2011). In this experiment direct regeneration from seed was done for obtaining 5 weeks old plantlets of kinnow and citron species.…”
Section: Direct Regeneration From Embryonic Seedmentioning
confidence: 99%
“…In turmeric, 2.5-3.0 mg/L of 2,4-D was found to be optimum for callus induction and callus was initiated within two weeks of culture [45]. Similarly, Savita et al [46] reported maximum callus induction of 98.66% from leaf segments on MS medium supplemented with four mg/L 2,4-D in Citrus jambhiri and Citrus sinensis [47].…”
Section: Discussionmentioning
confidence: 99%